IMPLEMENTASI PROGRAM KOTA LAYAK ANAK DENGAN PENDEKATAN KELURAHAN RAMAH ANAK DI KECAMATAN GAYAMSARI - Anindya Rachmania; Ari Subowo; Dewi Rostyaningsih (Journal of Public Policy and Management Review, 2015)
Semarang Local Government accelerate the realization of the development of Child Friendly City/Regency by creating mayor regulations number 20 year 2010 concerning child friendly policy using child friendly village approach, afterward follow up with the Regional Action Plan and Semarang mayor’s decision number 050/425 concern in determining the location of District Pilot Program in Semarang City in 2011-2015. Gayamsari Sub-district is chosen as the pilot of child friendly sub-district hereafter implement derivatives regulation that is child-friendly village, held in Gayamsari Sub-district. Even though has already set as the pilot child friendly village, however Gayamsari District still has low numbers of APK APM and low numbers of child welfare compared with other pilot districts. The research goal is to find out how to the program implementation of Child Friendly using Child Friendly Village Approach undertaken by Gayamsari Village using success indicator from RAD and PERWAL, also supporting factors and resistor factors of program implementation. This research uses the theory of George C. Edward III. The methods of this research uses qualitative research in descriptive type. The result of this research, the clusters of civil rights and freedoms, family environment and the right clusters alternative, clusters of education and utilization of leisure and arts activities, not in accordance with the indicators of success, Whereas the right cluster of basic health and welfare, and special protection cluster implementation is in conformity with the indicators of success. Driving factor of this implementation is a bureaucratic structure and disposition of the cadres, while the inhibiting factor of resources, communication, and the disposition of the employees of district and village The conclusion of this research program implementation KLA using Child Friendly Village approach in Gayamsari Village has not succeed yet. Because there are still several success indications has not fulfilled yet. Therefore, there are the factors which inhibits program implementation. It needs to be improved in manufacturing RAD, the communication between Semarang Government, Sub-district, Village, also the improvement in financial resources and disposition employees in village and sub-district.